Mandalay - city of Buddha, centre of diversity, or whose city now? - Hudson-Rodd, Nancy (Faculty of Social Sciences and Humanities, UKM,Bangi, 2005)
Mandalay, a multi-cultural city was a globally connected city in the 19th century. It has undergone many changes since its creation (occupation by British and Japanese) isolation during the socialist reign and now is in the process of another grand cultural re-formation through the work of the military ruling elite who seek to promote the ‘real Myanmar cultural heritage’. This paper aims to understand and expose the multiple cultural heritages of Mandalay as identified and described in the terms of the contemporary residents of the city. It is proposed that while the distinct and characteristically unique Burmese feature of Mandalay lies in its universal Buddhist peaceful potential, its complex multiplicity of life’s meanings, and its impermanence,Mandalay now represents a city of many separate lives as a result of a brief 150 years of transformations.The paper concludes that the complexity of urban cultural heritage demonstrates that no one simplistic perspective of urban identity makes sense for Mandalay. Life here is a tangle of an elusive cultural heritage